Analisis Faktor-Faktor Yang Mempengaruhi Kemiskinan di Sumatera Utara - Purba, Kristin Yenita; Clawdya Zebua, Nobel Indah; Manurung, Zenifer (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to analyze the effects of unemployment, inflation and investment on poverty in North Sumatra in 1991-2020. This study uses time series data obtained from the Central Bureau of Statistics of North Sumatra. This study uses the Error Correction Model (ECM) analysis method. To determine the effect of the independent variables on the dependent variable in the short term and Multiple Linear Regression to determine the effect of the independent variables on the dependent in the long term. From the results of the ECM estimation or short-term analysis, it shows that the inflation variable has a significant and positive effect on the poverty rate in North Sumatra. In the long term, the unemployment variable is proven to have a significant and positive effect on poverty. On the other hand, in the short term it is also proven that changes in unemployment have a significant and positive effect on poverty. In the long run, the investment variable is proven to have a significant and positive effect on poverty.